Black Soldier Fly (Hermetia illucens) pre-pupae meal as a fish meal replacement in diet for amur carp (Cyprinus carpio) - Panikar, Preetha; Amla, U; Jesna, P K; Khan, M Feroz; Das, B K; Chandish, R. Ballal; Hassan, M. A. (Journal of the Inland Fisheries Society of India, 2019)
A feeding trial was conducted to evaluate the potential of complete and partial replacement of fish meal (FM) with Black Soldier Fly (Hermetia illucens) pre-pupae meal (BSFM) incorporated feed for Amur carp (Cyprinus carpio). Four different types of feed prepared with 0, 30, 70 and 100 % replacement of fish meal with sun dried BSF pre-pupae were provided. Thefishes were fed the diets twice per day at a daily feeding rate of 10 % of biomass over a period of 90 days. Percentage weight gain, specific growth rate (SGR), survival, feed conversion ratio (FCR) and feed efficiencyratio (FER) were estimated to analyse the growth performance of the experimental animal. There were no significant differences (P≤0.05) in growth performance among fishes fed different diets with up to 70% fishmeal replacement. However, fish fed diet with 100% replacement of fish meal had significantly lower growth with significantly lowest (P≤0.05) average final weight (8.750a± 0.127), mean weight gain (6.560a±0.140),percentage weight gain (299a± 5.66) and specific growth rate (1.540a±0.018). Lowest FCR (2.18a±0.08) was recorded in fishes fed diet with 0% fish meal replacement which was statistically different (P≤0.05)from the treatment with 70% fish meal replacement. The results of the study indicate that up to 70% fish meal can be replaced with BSFM without affecting growth and survival of Amur carp fingerlings.Keywords Cyprinus carpio, Black Soldier Fly, Hermetia illucens, Growth, Amur carp